The complete mitochondrial genome sequence of Eophona migratoria (Passeriformes Fringillidae). Issue 1 (1st January 2016) - Sun, Guolei; Xia, Tian; Yang, Xiufeng; Zhao, Chao; Liu, Guangshuai; Sha, Weilai; Zhang, Honghai
Abstract: The complete mitochondrial genome (mitogenome) sequence of Eophona migratoria was determined by shotgun sequencing and reported for the first time using the muscle tissue. The total length of the sequence is 16, 798 bp, which contains 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, 1 control region, and 1 extra pseudo-control region. A phylogenetic analysis on the basis of 12 protein-coding genes of 14 passeriformes species' mitochondrial genomes using maximum-likelihood (ML) demonstrated that Coccothraustes coccothraustes is the most close to E. migratoria .